Energetic Simulation of Complex Mechatronic Drive Systems over Complete Drive Cycles - Hörlin, Sebastian; Dietz, Armin; Hubert, Markus; Franke, Jörg (Applied Mechanics and Materials, 2015)
This paper presents a simulation model, which enables the energetic simulation of complex mechatronic powertrains over complete drive cycles. One focus of this work is on reducing the simulation duration to enable the simulation of extended drive cycles on the one hand, and the possibility to optimize drive cycles on the other hand. Furthermore, the program allows the user to assemble an energetically optimized selection of propulsion components.